Coppery titi monkey (Plecturocebus cupreus) pairs display coordinated behaviors in response to a simulated intruder. Issue 7 (16th May 2020) - Mercier, Fanny; Witczak, Lynea R.; Bales, Karen L.
Abstract: Mate guarding and coordinated behaviors between partners are important for the maintenance of monogamous pair bonds. To study the effects of a perceived unfamiliar social intruder on females' behavior, we used coppery titi monkeys ( Plecturocebus cupreus ). We examined the effects of male aggressive temperament on females' behavior and the effects of each behavior performed by the male on the same female behavior. Using a mirror, we simulated a social intruder in the home territory and scored behaviors using an established ethogram. Based on our analysis of self‐directed behaviors, females do not recognize themselves in the mirror. We then used general linear mixed models to predict percent change in females' behaviors as a function of (a) males' temperament, (b) males' behavior, and (c) an interaction between males' temperament and behavior. Male temperament did not significantly predict female behavior for any of our best fitting models. For percent change in female lip‐smacking, male lip‐smacking significantly predicted female lip‐smacking ( β = 0.74, SE = 0.22, t = 3.39; p = .004). There was a positive correlation between male and female agonistic behaviors such as back‐arching/tail‐lashing ( β = 0.51, SE = 0.23, t = 2.22; p = .04) and for anxiety‐related behaviors such as leaving the partner ( β = 0.50, SE = 0.19, t = 2.68; p = .015), locomotion duration ( β = 0.19, SE = 0.06, t = 2.98; p = .02), and locomotion frequency ( β = 0.71, SE = 0.14, t = 5.17; p < .001). These findings on coordination of pair‐mate behaviors may explain how titi monkeys display pair bond strength and ensure their reproductive success. Abstract : Relationship between monogamous male and female coppery titi monkey ( Plecturocebus cupreus ) behavioral responses to a perceived intruder in the home territory. Males and females responded robustly to their reflections in the mirror and did not show evidence of self‐recognition. Affiliative (lip‐smacking), agonistic (back‐arching/tail‐lashing), and anxiety‐like (locomotion, breaking affiliation) displays were all positively correlated between partners. There was a nonsignificant trend toward females lip‐smacking less when paired with high‐aggressive males. This coordination of behaviors between pair‐mates may be a means of displaying pair bond strength and may ensure greater reproductive success by preventing intrusions of unfamiliar conspecifics. Greater synchrony of behaviors may also have protective buffering effects on pair‐mates and reduce the risk of adverse health outcomes.